ANALISIS PEMECAHAN MASALAH MATEMATIKA PERKALIAN PECAHAN DENGAN BILANGAN ASLI MENGGUNAKAN MODEL PBL BERBANTU SOAL CERITA BUDAYA PAPUA - Irawati; Wigati Yektiningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the mathematical problem-solving abilities of sixth-grade students in solving fraction multiplication with whole numbers through the implementation of the Problem Based Learning (PBL) model supported by story problems based on Papuan local wisdom at SD Negeri 01 Nabire. This research is motivated by the low level of students’ problem-solving abilities, particularly in solving contextual word problems that require conceptual understanding, reasoning, and the ability to relate mathematics to real-life situations. The study employed a qualitative approach with a descriptive design. The research subjects were selected purposively from Grade VI A students. Data collection techniques included observation, interviews, problem-solving tests, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of PBL supported by local wisdom-based story problems enhances students’ active engagement in the learning process. Students demonstrated improved abilities in understanding problems, devising plans, carrying out strategies, and reflecting on their solutions based on Polya’s stages. The integration of local cultural contexts such as sago processing, fishing activities, and communal sharing practices helped students grasp fraction concepts more concretely and meaningfully. Furthermore, students showed positive responses toward the learning process, as reflected in increased motivation and interest. Supporting factors included the relevance of local contexts, collaborative learning strategies in PBL, and the teacher’s role as a facilitator. Meanwhile, inhibiting factors involved limited instructional time, varying student abilities, and limited learning resources. Overall, problem-based learning integrated with Papuan local wisdom positively impacts students’ mathematical problem-solving abilities.